Narcissism, Self-Esteem and Social Desirability Bias - Vogronić, Nemanja; Gojković, Vesna (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
The aim of this study was to determine the relation of self-esteem and social desirability bias to narcissism. The study tested 218 examinees from Apatin and Novi Sad, average age 20 years, using questionnaires NPI-40 (narcissism), RSES (self-esteem) and MC-SDS (social desirability bias). The factor analyses results showed a tri-factor structure of narcissism, and a four-factor structure of social desirability bias. Contrary to expectations, narcissism was positively correlated with self-esteem and negatively correlated with the factors of social desirability bias. Self-esteem and social desirability bias were significantly, positively related. Narcissistically structured personalities are not trying to present themselves as conformists, because they are distinguished by antagonistic, dominant, and not by prosocial strategies of behaviour.